Journal of Contemporary Drama in English (De Gruyter, 2013)
The peer-reviewed journal focuses on issues in contemporary Anglophone dramatic literature and theatre performance. It renegotiates the understanding of contemporary aesthetics of drama and theatre by treating dramatic texts of the last fifty years. JCDE publishes essays that engage in close readings of plays and also touch upon historical, political, formal, theoretical and methodological aspects of contemporary drama, theatre and performance.